OPTIMASI SISTEM SALURAN TERHADAP CACAT SHRINKAGE PADA CASTING IMPELLER DENGAN METODE SIMULASI SAND CASTING - Joshua Ananda Mayki (2020)
The impeller is an important component that rotates in a centrifugal pump and has the function of converting mechanical energy from the pump to the kinetic fluid that is pumped constantly, so that the fluid on the inlet side will keep coming in to fill the void because of the previous fluid transfer. Aluminum is widely used in the manufacturing world because of the advantages of aluminum material. In making impellers using aluminum material through the sand casting process. The study was conducted to analyze the effect of two types of channels as well as variations in the diameter of the riser to shrinkage by making a model of the cast impeller product in 3D, then simulating it using a casting simulation software produced by the impeller. The simulation is carried out to reduce the occurrence of shrinkage defects in the impeller component in a simulation, so that the simulation results in the form of the location and percentage of shrinkage defects. Then the conclusion is that the number of inlet shows different shrinkage values, where the smallest percentage is seen in the two gating system which is 1.32% and in the variation of the riser diameter difference of the two gating systems is 1.31% shrinkage defect.